PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT BUDI ANUGRAH BERSAMA - Armansyah Putra; Rizali Hadi; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2021)
This study aims to examine the effect of the work environment (X) on employee performance (Y) at PT. Budi Anugrah Bersama. The approach taken is quantitative and type of research (explanatory research). The population and sample in the study were 61 people. Data collection techniques in the form of observation, interviews and questionnaires. Likert scale variables are examined. The questionnaire was tested with a validity test and a reliability test. Data processing using SPSS version 21.0, analyzed with descriptive statistical analysis and hypothesis testing with simple linear regression.The validity test results for the working environment are valid because r > 0.3 and the reliability test shows reliable because of alpha cronboarch> 0.6. Normality test is obtained at 0.05 and it is said that the data is normally distributed and on the normal line the plot shows the point of the graph spreading around the diagonal line and following the diagonal line.The conclusion of this study has a significant effect on the work environment by 72% on the performance of employees at PT.Budi Anugrah Bersama.Keywords: Working Environment, Employee Performance